Alinhamento entre estruturas de governança e atributos das transações na gestão estratégica da aquisição de farinha de trigo - Menita, Paulo Renato (2011)
Strategic decisions for the results of the companies have demanded the use of management tools that allow a better analysis of the context of the decision. The research used as tool for management purchasing the analysis of alignment between governance structures and the attributes of transactions. The environment where the research was developed it was the production chain of wheat in Brazil, more precisely the parts of the chain involved in transactions for the purchase of wheat flour. The research method used was a case study involving the company and its main ingredient, the wheat flour. The goals set for the research were to identify the transactions realized by the company for the purchase of wheat flour; analyze the alignment between governance structures and the attributes of these transactions, analyze if the transactions have impacted the results of this company demanding strategic management and consider if such transactions were generating new relationships between chain s members and if these transactions can define a new design for the production chain of wheat in Brazil. Data collection was performed during the second half of 2009 through interviews and a questionnaire addressing the topics of research. As results, the research identified four different types of transactions for the purchase of wheat flour and that the transactions can impact the results of the company studied, presented an analysis of alignment between governance structures and the attributes of these transactions, that this analysis is an important strategic management tool purchases and, finally, that these transactions made indicate new relationships and a new design for the production chain of wheat in Brazil.